Studi Keruangan Kedai Kopi dan Ekonomi Kognitif-Budaya di Kota Surakarta Tahun 2019 (Suplemen Materi Bahan Ajar Geografi SMA Kelas X Kurikulum 2013 pada Kompetensi Dasar 3.1. Memahami Pengetahuan Dasar Geografi dan Terapannya dalam Kehidupan Sehari–Hari) - Wahyu Trianingsih; Yasin Yusup; Rahning Utomowati (GEADIDAKTIKA, 2020)
This research aims to : (1) determine the distribution of coffee shops inSurakarta in 2019 (2) determine the relationship of coffee shop distribution witheconomic dominance in Surakarta in 2019 (3) determine the characteristics ofcoffee shop visitors in Surakarta in 2019. This research is a quantitative research.The approach in this study is a spatial approach is a map. the results of the researchit can be seen that : (1) The distribution of coffee shops is mostly found in LaweyanDistrict because Laweyan District is an urban center which is the center ofcommunity activity. (2) There is a positive correlation between the distribution ofcoffee shops with the dominance of cognitive-cultural economy. (3) Coffee shopvisitors are residents of productive age, including the upper middle class.